Some Illusions of Urban/Industrial Paradigm of Development - Ighalo, J. I. (Obafemi Awolowo University Press, 2013)
The main objective of this lecture, therefore, is to test the validity of the "trickle down" or "spread effect" notion embodied in the urban industrial paradigm of regional development by 'examining empirically the developmental impact of urban/industrial concentration on backward rural regions . This lecture focuses on urban industrial centres of Benin City, Warri and Sapele in the Old Bendel State, Nigeria (Now Edo and Delta States). The Old Bendel State provides a suitable test bed for examining the impact on backward rural regions of urban industrial concentration because these three urban industrial centres have witnessed considerable industrial growth in recent years. Warri and Sapele are national ports while Benin City was the administrative Capital of the old Bendel State. It is thus possible to contrast and compare the spatial impacts in more than one urban centre.